Pembuatan Pupuk Kompos Dari Limbah Sayuran Pada Kelompok Wanita Tani Seroja Di Desa Bedahlawak Tembelang Jombang - Yuyun Bahtiar; Mahardina Putri Teguh Laily; Nurul Latifatul Aini; Surya Andre Ferdian Causa (LOYALITAS: Jurnal Pengabdian Kepada Masyarakat, 2022)
The implementation of this community service activity was carried out by the implementing team in Bedahlawak village, Bedalawak sub-district, Jombang district. This service activity is in the form of an entrepreneurship seminar to help entrepreneurs (home industry) to be more enthusiastic in running a home business. The purpose of this activity is to help home industry entrepreneurs start from how to make hygienic products, how to make labels to attract buyers and how to package these products. The method used in the workshop as well as training and mentoring. The results of this service activity are very helpful for the Seroja Women's Farmer Group in Bedahlawak Village